Students’ Grammar and Vocabulary Mastery: Does It Correlate To Students’ Writing Skills? - Luthfiyati, Dian; Widyaiswara, Tiara; Anggraini, Zuli Dwi (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
The lack of vocabulary mastery often becomes an obstacle in writing, whereas vocabulary determines how skilled a person is in language. It is also supported by qualified grammatical skills so that the writing is directed and by existing rules, producing readable and coherent writing content. This study aims to describe pupils' essay writing skills and the link between grammar competence and vocabulary mastery. The study is ex post facto. The sample in this study is 104. The research data were obtained through three instruments: an essay text, a grammar mastery test, and a vocabulary mastery test. The data analysis technique used is product-moment correlation and multiple regression. Mastery of vocabulary and grammar together has a considerable impact on English Education students' essay writing skills; grammar competence considerably impacts English Education students' essay writing abilities; and vocabulary knowledge substantially impacts English Education students' essay writing abilities. It implies that mastery of vocabulary and grammar significantly impacts students' essay-writing abilities at Universitas Islam Lamongan.